Teaching Reading Descriptive Text by Using Tree Mapping for Senior High School Students - Katrina Vabiola; Fitrawati Fitrawati (Journal of English Language Teaching, 2018)
The teacher can use tree mapping in teaching reading descriptive text in the teaching and learning process. By applying this technique, the students can get interest and understand the descriptive text well. The objective of this paper is to help the students to organize their ideas and write the ideas in a good order. Besides that, the teacher also has to give more time for teaching reading especially in teaching text in order to increase the students’ ability in reading descriptive text. Reading descriptive text through tree mapping brings the students to new kind of situation. It would help both the teacher and the students to revise the students’ reading method and made reading more fun than the way it used to be.